DNA damage induced by fotemustine in cultured HL60 cells - Shou Jiang; Feng Xing-Wan (Acta Pharmacologica Sinica, 2016)
"AIM: To detect DNA damage caused by fotemustine (Fot). METHODS: DNA damage in HL60 cells was evaluated by modified alkaline elution technique. DNA interstrand crosslink (ISC) and DNA-protein crosslink (DPC) were determined. Carmustine (Car) was used as control. Drug treatment time was 1 h. RESULTS: After treatment with Fot 300 mumol.L-1, ISC and DPC index were 5.4 and 6.1 at 6 h, 2.7 and 1.2 at 12 h, respectively. ISC reached the maximum at about 6 h. For Fot 100 mumol.L-1, ISC and DPC index at ISC peak time were 2.1 +/- 0.9 and 3.55 +/- 0.23, 5.0 +/- 0.5 and 7.7 +/- 1.1 for Car 100 mumol.L-1, respectively. Single strand break (SSB) was induced by Fot. CONCLUSION: Fot caused HL60 cell DNA ISC, DPC, and SSB. ISC was formed more quickly by Fot than that by Car. "